From Glasgow to Bilbao: Bible John’s Fictional Journey in Dolores Redondo’s Esperando al diluvio (2022) - Domènech, Conxita (2024)
In Esperando al diluvio, Dolores Redondo uses a serial killer from the late 1960s who was never arrested or even identified, Bible John, and moves him from Glasgow to Bilbao, followed by the detective investigating the case. In this article, I will analyze this and all the journeys that Redondo incorporates in the novel: the author’s own nostalgic journey; the journey towards a new detective —or profiler—; the journey to the Bilbao of the eighties; and the experimental journey of the new crime novel. All these journeys are intertwined in a work that constantly moves from fiction to reality and, also, to the personal. While Esperando al diluvio is neither a biographical nor an autobiographical novel, the biographical elements of Bible John are present, as are those of Joe Beattie—the detective who investigated the case in real life and whom Redondo calls Noah Scott Sherrington. Furthermore, Esperando al diluvio includes autobiographical information: after the success of the Baztán Trilogy, and winning the Planeta Prize for Todo esto te daré, Redondo experiments with a novel that will finally help her to make peace with her own past.